Transient submillimeter-scale periodic banding of Ag2O precipitate through reaction–transport–reaction processes - Hayashi, Hisashi; Yamada, Kaho (Frontiers in Physics, 2024)
We describe a new class of the periodic banding of Ag2O precipitates through reaction-transportreaction processes in an agarose-hydrogel column; the gel contains NaNO3 as an additive and is inserted between Ag and Ti rods with an applied constant voltage of 4.0-7.0 V. Submillimeterscale periodic dark-brown precipitation bands were transiently generated with high reproducibility in this system, in which (i) electrochemical reactions at the metal rods to generate Ag + and OH -, (ii) transportation of the reactant ions by the electric field, and (iii) reactions to produce Ag2O are expected to couple. The bands successively emerged mainly toward the cathode, accompanied by substantial changes in the electric current through the gel. The periodic banding depended on the applied voltage, duration of application, and concentration of NaNO3 initially loaded in the gel. The banding was most clearly observed in a 2.0 mass% agarose gel column containing 0.005 M NaNO3 under a constant applied voltage of 5.5 V for 3 h. This optimal condition resulted in more than ten periodic bands, of which the bandwidth (w) and the distance between the adjacent bands (d) were randomly distributed around the average values: for the bands formed up to 2 h, w = 0.25 ± 0.04 mm and d = 0.42 ± 0.05 mm; for the bands formed after 2 h, w = 0.42 ± 0.11 mm and d = 0.68 ± 0.07 mm. The generated periodic bands were gradually painted out with time to form an almost continuous broad band, even after the applied voltage was discontinued, although immersion of the gel in deionized water for 3 h could suppress this uniformization. Observations using optical and scanning electron microscopes with an energy-dispersive X-ray detector suggested that the periodic bands were composed of gelatinous Ag2O and micrometer-scale (1-50 μm) clusters, which comprised Ag-abundant nanoparticles with considerable size dispersion (10-500 nm). The relationship between the periodic banding and inhomogeneous distribution of the reactant ions and potential applications of the observed banding phenomena are discussed.